Cytogenetic Analysis Did Not Reveal Differentiated Sex Chromosomes in Ten Species of Boas and Pythons (Reptilia: Serpentes) - Augstenová, Barbora; Mazzoleni, Sofia; Kostmann, Alexander; Altmanová, Marie; Frynta, Daniel; Kratochvíl, Lukáš; Rovatsos, Michail (Genes, 2019)
Homologous and differentiated ZZ/ZW sex chromosomes (or derived multiple neo-sex chromosomes) were often described in caenophidian snakes, but sex chromosomes were unknown until recently in non-caenophidian snakes. Previous studies revealed that two species of boas (Boa imperator, B. constrictor) and one species of python (Python bivittatus) independently evolved XX/XY sex chromosomes. In addition, heteromorphic ZZ/ZW sex chromosomes were recently revealed in the Madagascar boa (Acrantophis sp. cf. dumerili) and putatively also in the blind snake Myriopholis macrorhyncha. Since the evolution of sex chromosomes in non-caenophidian snakes seems to be more complex than previously thought, we examined ten species of pythons and boas representing the families Boidae, Calabariidae, Candoiidae, Charinidae, Pythonidae, and Sanziniidae by conventional and molecular cytogenetic methods, aiming to reveal their sex chromosomes. Our results show that all examined species do not possess sex-specific differences in their genomes detectable by the applied cytogenetic methods, indicating the presence of poorly differentiated sex chromosomes or even the absence of sex chromosomes. Interestingly, fluorescence in situ hybridization with telomeric repeats revealed extensive distribution of interstitial telomeric repeats in eight species, which are likely a consequence of intra-chromosomal rearrangements.
Keywords: Sex Chromosomes; Male; pohlavní chromozomy; karyotypizace; microsatellites; hybridizace in situ fluorescenční; Boidae; boa; genová přestavba; Sex Determination Processes; telomeres; sex determination; Karyotyping; molekulární evoluce; Evolution, Molecular; mužské pohlaví; rDNA; genom; sex chromosomes; Animals; ženské pohlaví; Gene Rearrangement; fluorescence in situ hybridization; evolution; telomery; zvířata; In Situ Hybridization, Fluorescence; Genome; procesy určující pohlaví; python; Female; comparative genomic hybridization; karyotype; Telomere